Steneotarsonemus spinki Smiley (Acari: Tarsonemidae): Nuevo informe para Cuba - Ramos, M.=700 1 Rodriguez, H.
(Es, En)
Ilus., 5 ref.
Keywords: STENEOTARSONEMUS; ACARINA; TARSONEMIDAE; QRROZ; PHYTOSEIIDAE; CUBA; REVISTA DE PROTECCION VEGETAL